2013
DOI: 10.3109/09593985.2013.870267
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability of select physical examination procedures in patients with neck pain

Abstract: This study evaluated the inter-rater reliability of select examination procedures in patients with neck pain (NP) conducted over a 24- to 48-h period. Twenty-two patients with mechanical NP participated in a standardized examination. One examiner performed standardized examination procedures and a second blinded examiner repeated the procedures 24-48 h later with no treatment administered between examinations. Inter-rater reliability was calculated with the Cohen Kappa and weighted Kappa for ordinal data while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…It has been suggested that Kappa values above 80% demonstrate excellent agreement, values from 60% to 80% substantial levels of agreement, values from 40% to 60% moderate agreement, and values below 40% poor to fair agreement. 17 The x 2 test was used to analyze the prevalence of right or left head positional preference and the side prevalence of the active and passive cervical rotation and the passive lateral flexion. The severity of ROM limitations was assessed by means of x 2 test.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Kappa values above 80% demonstrate excellent agreement, values from 60% to 80% substantial levels of agreement, values from 40% to 60% moderate agreement, and values below 40% poor to fair agreement. 17 The x 2 test was used to analyze the prevalence of right or left head positional preference and the side prevalence of the active and passive cervical rotation and the passive lateral flexion. The severity of ROM limitations was assessed by means of x 2 test.…”
Section: Discussionmentioning
confidence: 99%
“…A bubble inclinometer was used for all AROM directions (except hand‐behind‐back). This method showed moderate to high test‐retest and intratester reliability at the shoulder and cervical spine 20‐23 . Hand‐behind‐back is a composite measure of shoulder internal rotation, extension, and adduction and was rated with reference to the hand reaching the opposite scapula (0), 6 to 15 cm beneath the opposite scapula (1), the opposite iliac crest (2), or the buttock (3) or being unable to move behind the trunk (4) 24 .…”
Section: Methodsmentioning
confidence: 99%
“…This method showed moderate to high test-retest and intratester reliability at the shoulder and cervical spine. [20][21][22][23] Hand-behind-back is a composite measure of shoulder internal rotation, extension, and adduction and was rated with reference to the hand reaching the opposite scapula (0), 6 to 15 cm beneath the opposite scapula (1), the opposite iliac crest (2), or the buttock (3) or being unable to move behind the trunk (4). 24 Participants performed 3 practice trials and then 3 repetitions of each test, with the mean of the 3 repetitions used for analysis.…”
Section: Measures Of Motor Functionmentioning
confidence: 99%
“…All other AROM measurements were taken with a bubble inclinometer. These measurements have demonstrated moderate to high test-rest and intra-tester reliability [24][25][26][27]. Three practice trials for each movement were conducted, after which three repetitions were recorded and the mean used for analysis.…”
Section: Shoulder and Neck Active Range Of Motion (Arom)mentioning
confidence: 99%